Improving research quality on primary cam morphology - Dijkstra, HP (2023)
Introduction: Primary cam morphology—a cartilage or bony prominence at the head-neck junction of the hip—develops due to high-load sporting activity during maturation. Although prevalent in many athlete populations, this morphology generally occurs without ill-effects; however, some individuals develop femoroacetabular impingement syndrome or hip osteoarthritis. Existing research on primary cam morphology and its natural history is mired in confusion partly because clinicians, athletes, patients, and researchers have not agreed on key primary cam morphology elements or a prioritised research agenda.